2007
DOI: 10.1073/pnas.0702715104
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Plasmodium falciparum in the two main African vectors, Anopheles gambiae and Anopheles funestus

Abstract: We investigated patterns of genetic diversity of Plasmodium falciparum associated with its two main African vectors: Anopheles gambiae and Anopheles funestus. We dissected 10,296 wildcaught mosquitoes from three tropical sites, two in Cameroon (Simbock and Tibati, separated by 320 km) and one in Kenya (Rota, >2,000 km from the other two sites). We assayed seven microsatellite loci in 746 oocysts from 183 infected mosquito guts. Genetic polymorphism was very high in parasites isolated from both vector species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 54 publications
11
58
0
Order By: Relevance
“…That selfing and inbreeding amount to clonality is a view shared by most authors working on Plasmodium (Anderson et al, 2000;Annan et al, 2007;Beck et al, 2009;Conway, 2007;Griffing et al, 2011;Mu et al, 2005;Mzilahowa et al, 2007;Nkhoma et al, 2013;Razakandrainibe et al, 2005;Volkman et al, 2012a) and Toxoplasma (Beck et al, 2009;Grigg and Sundar, 2009;Lehmann et al, 2004;Sibley and Ajioka, 2008;Su et al, 2012;Wendte et al, 2010). However, clonality does not limit itself to selfing and inbreeding and can have other origins (mitotic propagation and several cases of parthenogenesis, gynogenesis, and hybridogenesis).…”
Section: Indispensable Recallsmentioning
confidence: 99%
See 1 more Smart Citation
“…That selfing and inbreeding amount to clonality is a view shared by most authors working on Plasmodium (Anderson et al, 2000;Annan et al, 2007;Beck et al, 2009;Conway, 2007;Griffing et al, 2011;Mu et al, 2005;Mzilahowa et al, 2007;Nkhoma et al, 2013;Razakandrainibe et al, 2005;Volkman et al, 2012a) and Toxoplasma (Beck et al, 2009;Grigg and Sundar, 2009;Lehmann et al, 2004;Sibley and Ajioka, 2008;Su et al, 2012;Wendte et al, 2010). However, clonality does not limit itself to selfing and inbreeding and can have other origins (mitotic propagation and several cases of parthenogenesis, gynogenesis, and hybridogenesis).…”
Section: Indispensable Recallsmentioning
confidence: 99%
“…Discussions of pathogen population structure have focused on the "clonality/sexuality debate" (Tibayrenc et al, 1990). Clonality is here understood as scarcity or absence of genetic recombination, a definition widely accepted for all kinds of pathogens (Tibayrenc and Ayala, 2012), including Plasmodium (Anderson et al, 2000;Annan et al, 2007;Beck et al, 2009;Conway, 2007;Griffing et al, 2011;Heitman, 2006;Mu et al, 2005;Nkhoma et al, 2013;Razakandrainibe et al, 2005;Volkman et al, 2012a) and Toxoplasma (Beck et al, 2009;Heitman, 2006;Khan et al, 2011;Rajendran et al, 2012;Sibley and Ajioka, 2008;Smith, 2009;Su et al, 2003Su et al, , 2010Wendte et al, 2011). Clonality does not amount to genetic monomorphism, an erroneous definition still used by some researchers (Tibayrenc and Ayala, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Again, the few studies that have analysed the genetic variability of oocyst infrapopulations found strong genetic differentiation between them (Razakandrainibe et al, 2005;Annan et al, 2007). Several aspects of parasite biology or of their hosts may explain the amount of genetic differentiation observed between oocyst infrapopulations.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have analysed it within natural oocyst infrapopulations reported high positive values (Paul et al, 1995;Razakandrainibe et al, 2005;Annan et al, 2007;Mzilahowa et al, 2007), meaning that infrapopulations harboured more homozygous individuals than expected if gametes had met at random. Two main hypotheses are generally proposed to explain a positive F IS (in our model, F IM ) in oocyst infrapopulations: selffertilization and/or Wahlund effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation